Diseño e implementación de manual didáctico para disminuir la mala ortografía en el grado 3° del CEIR HABÍA HONDITA Sede Mauripao. (2020)
The objective of this study is to design, evaluate and apply an orthographic teaching manual for the strengthening of spelling in the 3rd grade students of CEIR Bahía Hondita, Mauripao campus. The present research was classified as a feasible project with a qualitative approach of a descriptive type, structured questionnaires were used from the cognitive, procedural and behavioral aspects to know the main aspects in the use of spelling rules. Through the analysis of the results, it was possible to identify the main causes of problems that the third grade students of spelling present in the 3rd grade students of the CEIR Bahía Hondita, Mauripao campus, by writing short papers using the spelling rules in an appropriate way. It was concluded that the index of the correct use of grammar rules is of very poor quality in the third grade students of CEIR of Bahia Hondita Sede Mauripao, urgently needing to develop and implement new didactic manuals, which have to find the differential ethnic focus of the culture and region, which is one of the main barriers to learning a language that is not their mother tongue. Therefore, a didactic model is proposed that covers the shortcomings present in the current learning models.